If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -4) = 2(2x + 5) Reorder the terms: 5(-4 + x) = 2(2x + 5) (-4 * 5 + x * 5) = 2(2x + 5) (-20 + 5x) = 2(2x + 5) Reorder the terms: -20 + 5x = 2(5 + 2x) -20 + 5x = (5 * 2 + 2x * 2) -20 + 5x = (10 + 4x) Solving -20 + 5x = 10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -20 + 5x + -4x = 10 + 4x + -4x Combine like terms: 5x + -4x = 1x -20 + 1x = 10 + 4x + -4x Combine like terms: 4x + -4x = 0 -20 + 1x = 10 + 0 -20 + 1x = 10 Add '20' to each side of the equation. -20 + 20 + 1x = 10 + 20 Combine like terms: -20 + 20 = 0 0 + 1x = 10 + 20 1x = 10 + 20 Combine like terms: 10 + 20 = 30 1x = 30 Divide each side by '1'. x = 30 Simplifying x = 30
| 3x+10=2x+10 | | (x+1)(x-5)(x-7)=0 | | f+(-3)=9 | | 2y=-5y-49 | | -14+y=2 | | -4(t-3)-2(-7t-8)=9(t+2)+4 | | 36(x-144)=72 | | 15x+26-2x=6x+61 | | b-2=11 | | 5x=-5x+10 | | 3-4q=-5+8q | | 7y^3+5y^2= | | -4(t-3)-2(7t-8)=9(t+2)+4 | | 11x-2y+12w-6y-2w+2x= | | 9h+7-6h=-5+9 | | 6-2(3x-2)=14 | | 1/2(w+1)=9 | | 6a^2x^2+11a^2x+4a^2= | | 4v-2(3-v)=-13 | | 14-y=5 | | 4(b-1)=-4+b | | 5x-(2x-2)=x+(3x-5) | | 5x-6=2x+21 | | 49-2x=7x+17 | | 19-(2x-2)=5 | | 5-2x=-4x(2x+1) | | 5-9x=55-23x | | (3/15)y+15=0 | | 0.5x^2+0.375x+2=0 | | 6x-4=13x-56 | | -0.2x+0.5x+7=1 | | 8y+4=24-4 |